Implementation of Nursing Care by Providing Nebulizers to Asthmatic Children with Ineffective Airway Clearance Problems - Biladiah, Imadatul; Yunike; Jawiah (Yayasan Rumah Ilmu Professor, 2022)
Asthma is one of the main non-communicable diseases and asthma is a chronic disease in which the airways of the lungs become inflamed and narrow. Asthma trigger factors are often found in the environment both inside and outside the home, but children with a family history of asthma have a greater risk of developing asthma. Apart from that, factors that trigger asthma are divided into two groups, namely genetic, including bronchial atopy/allergy, eczema; environmental trigger factors, such as motor vehicle fumes, cigarette smoke, burning rubbish, humidity in the house, and allergens such as house dust and animal dander. Method: The case study used in this research is descriptive in a case study design to explore the implementation of nursing care providing nebulizers with the problem of ineffective airway clearance in children with asthma at Bhayangkara Hospital, Palembang. The approach used is a nursing care approach which includes assessment, nursing diagnosis, nursing intervention, nursing implementation, and nursing evaluation. Results: The results of the research after the implementation of asthma management nursing with a Nebulizer in Asthma patients were proven to have an impact on improving breathing frequency because it had the effect of improving sputum production so that it was very influential in the process of improving breathing frequency/shortness of breath. Conclusion: Implementation of Nursing Care by Giving Nebulizers to asthmatic children with hygiene problems ineffective airway can be done because it is more effective for asthma patients and improves respiratory frequency.